Combined high grade sarcoma and serous ovarian neoplasm. Issue 3 (March 1992) - Allen, C; Stephens, M; Williams, J
Abstract : A case of an ovarian serous epithelial neoplasm of borderline type admixed with sarcomatous elements is reported. This combination seems to be extremely rare with only four cases previously reported. It may represent a type of collision tumour or the development of a sarcoma in a growth with borderline differentiation.